Ken uw zelf - Perls, Frederick S., 1893-1970; Geluk, Hans L. Chr.; Goodman, Paul, 1911-1972; Hefferline, Ralph F., 1910-1974; Mesker, Rosalie (Den Haag : Bakker, 1972)
De gestalttherapie komt in dit boek uitgebreid aan bod.
2. De theorie / vert. door Rosalie Mesker